Implementasi Program Penanggulangan Tuberkulosis Paru - Sofiyatun, Vivi (HIGEIA (Journal of Public Health Research and Development), 2019)
ABSTRACT Introduction: the successful implementation of Tuberculosis prevention program is determined by the coverage of case finding rates and the success of the patient's treatment. At the Tlogosari Kulon health center, the number of coverage does not demand target. Purpose: Researchers want to analyze the implementation of Pulmonary Tuberculosis control program at the Tlogosari Kulon health center in 2018. Method: Qualitative research with descriptive design where the informants were selected by purposive sampling technique. Discussion: The lack of staff and facility resources, lack of consistency in communication and programmer commitment to patients that are less able to impede implementation so that they cannot reach the target set. Lack of active case discovery and information transmission that is only carried out between individuals makes the level of public knowledge low. Too loose commitment to patients can reduce treatment success rates. Conclusion: The implementation of the Tuberculosis prevention program at the Tlogosari Kulon health center is good enough but there are several factors that need to be corrected. At sains this reseach add knowledge about implmentation of Tuberculosis prevention program. Keywords: Implementation, Program, Tuberculosis